2011
DOI: 10.1039/c1cc13895b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled layered hybrid [Ru(bpy)3]2+/manganese(iii,iv) oxide: a new and efficient strategy for water oxidation

Abstract: For the first time, a self-assembled layered hybrid [Ru(bpy)(3)](2+)/manganese(III,IV) as a water oxidizing system is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…[28] On the other hand, delithiation of nanocrystalline LiMn 2 O 4 with dilute nitric acid produced l-MnO 2 . [43] Manganese oxide nanoclusters supported on the mesoporous silica KIT-6 were employed for the stacking of catalytic particles to attain a high rate of oxygen production per metal center as well as per projected geometrical area. Systematic studies by Jiao and co-workers showed that replacing metal ion from K-d-MnO 2 nanoparticles by Na + produced isostructured Na-d-MnO 2 which has comparable photochemical water oxidation activities.…”
Section: Photo-assisted Water Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] On the other hand, delithiation of nanocrystalline LiMn 2 O 4 with dilute nitric acid produced l-MnO 2 . [43] Manganese oxide nanoclusters supported on the mesoporous silica KIT-6 were employed for the stacking of catalytic particles to attain a high rate of oxygen production per metal center as well as per projected geometrical area. Systematic studies by Jiao and co-workers showed that replacing metal ion from K-d-MnO 2 nanoparticles by Na + produced isostructured Na-d-MnO 2 which has comparable photochemical water oxidation activities.…”
Section: Photo-assisted Water Oxidationmentioning
confidence: 99%
“…[29c] A close contact of the catalyst and the photosensitizer by the self-assembly of cationic [Ru(bpy) 3 ] 2 + between layers of anionic Mn III,IV oxide was also demonstrated. [43] Manganese oxide nanoclusters supported on the mesoporous silica KIT-6 were employed for the stacking of catalytic particles to attain a high rate of oxygen production per metal center as well as per projected geometrical area. [32] In line with the recent trend of using amorphous materials for catalytic reactions, Suib and co-workers reported higher TON for chemical and photochemical water oxidation with amorphous manganese oxide compared to tunnel and layered structures.…”
Section: Photo-assisted Water Oxidationmentioning
confidence: 99%
“…The procedure is simple and produced an efficient catalyst (0. 54 O labelling studies proved that water was the source of dioxygen [79].…”
Section: Amorphous Manganese Oxidementioning
confidence: 98%
“…Mn oxides were reported as water-oxidizing catalysts for artificial photosynthetic systems [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Among Mn oxides, nanolayered Mn oxides with different organic or inorganic ions between layers are efficient and stable in water oxidation [41].…”
Section: Introductionmentioning
confidence: 99%